2013
DOI: 10.1016/j.resp.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation, diaphragm weakness and weaning: A rehabilitation perspective

Abstract: Most patients are easily liberated from mechanical ventilation (MV) following resolution of respiratory failure and a successful trial of spontaneous breathing, but about 25% of patients experience difficult weaning. MV use leads to cellular changes and weakness, which has been linked to weaning difficulties and has been labeled ventilator induced diaphragm dysfunction (VIDD). Aggravating factors in human studies with prolonged weaning include malnutrition, chronic electrolyte abnormalities, hyperglycemia, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 77 publications
(92 reference statements)
0
25
0
2
Order By: Relevance
“…Ventilator induced diaphragm dysfunction is present in up to 50% of mechanically ventilated adults, and leads to impaired weaning and extubation failure (2325, 27, 28, 3335). While many adult studies use diaphragm ultrasound (23, 27, 28, 36, 37), we used a direct measure of strength (aPiMax), and found that that respiratory muscle weakness is nearly as common in children (35%).…”
Section: Discussionmentioning
confidence: 99%
“…Ventilator induced diaphragm dysfunction is present in up to 50% of mechanically ventilated adults, and leads to impaired weaning and extubation failure (2325, 27, 28, 3335). While many adult studies use diaphragm ultrasound (23, 27, 28, 36, 37), we used a direct measure of strength (aPiMax), and found that that respiratory muscle weakness is nearly as common in children (35%).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, once the respiratory failure and the other sources of instability are solved, the weaning process from the mechanical ventilation can be started. Weaning takes about 40% of the time spent on the ventilator and it is further complicated and delayed by additional problems in 20 to 30% of mechanically ventilated patients (BouAkl et al, 2012;Daniel Martin et al, 2013;McConville and Kress, 2012). Complicated weaning increases the ICU stay by 50% with elderly patients being more severely affected than the young (Crul et al, 2013;Esteban et al, 2002;Zarzhevsky et al, 2001aZarzhevsky et al, , 2001b.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors who have studied diaphragm strength invasively have reported that patients with greater diaphragm strength are more likely to successfully wean than patients with weaker diaphragms [ 75 , 76 ]. Animal and limited human studies have found that anti-oxidants and physical activity can block or attenuate ventilator-induced diaphragm dysfunction by short-term mechanical ventilation use [ 77 ], but more work investigating cellular and functional changes in the human diaphragm following mechanical ventilation is needed.…”
Section: Diagnosis and Prognosis In Acute Respiratory Distress Syndromentioning
confidence: 99%